en - Anak Agung Ratu Paratistha, Wijayanti; Widiastuti, Ni Made Ayu (e-Journal of Linguistics; Vol 15 No 2 (2021): enDO - 10.24843/e-jl.2021.v15.i02.p14, 2021)
This study entitled “Direct and Indirect Expressive Illocutionary Acts in the Movie Onward” is concerned with identifying the direct and indirect expressive types of illocutionary acts and also explain and analyze the meaning of the utterances interpreted by the hearers. The data were taken from a movie entitled Onward since many utterances were identified as expressive of illocutionary acts. The observation and documentation method used in collecting the data since the data are obtained from a spoken source like a movie. The method used in analyzing the data was descriptive qualitative since this study was intended to analyze social phenomena like speech acts. Two theories used in analyzing the problems. The first theory is proposed by Searle (1976) to analyze the type of expressive illocutionary acts. The second theory is proposed by Dell Hymes (1972) about context of the situation (S-P-E-A-K-I-N-G model) to analyze the meaning of expressive illocutionary acts hearers can interpret. Based on the analysis, there were six expressive types of illocutionary acts found in the movie: Thanking, Apologizing, Congratulating, Greeting, Wishing, and Attitude. In this study, we found all of the six types of direct and indirect expressive in the movie Onward. The hearers interpret the meaning of the utterance depending on context of situation consisting of setting and scene, participants, ends, act sequence, key, instrumentalities, norm, and genre.